Core–shell behavior and exchange bias of Fe-doped CuO nanoparticles - Oliveira, Aline Alves (2021)
Cu1−xFexO nanoparticles were prepared using a freeze-drying process followed by heat treatment. The particles were then characterized using Mössbauer spectroscopy and magnetization techniques. The results revealed complex magnetic behavior, which can be attributed to the presence of two different magnetic regions: the particle core, which has antiferromagnetic fluctuations, and the particle shell, where uncompensated spins are responsible for their superparamagnetic characteristics. At low temperatures, the moments freeze, revealing a ferromagnetic order for the shells and a dipolar magnetic interaction among the nanoparticles. In addition, an exchange-bias field revealed magnetic interactions between the core and the shell of the nanoparticles. The ferromagnetism observed in this system suggests that antiferromagnetic oxide matrices can be used for diluted magnetic semiconductor applications, if suitably doped.